Hypertensive intracerebral hemorrhage: Which one should we choose between laser navigation and 3D navigation mold? - Yuan, Zhengbo; Wang, Qingbo; Sun, Qikai; Li, Chenglong; Xiong, Fengzhen; Li, Zefu (Frontiers in Surgery, 2023)
Abstract Background: Hypertensive intracerebral hemorrhage (HICH) is a severe life-threatening disease, and its incidence has gradually increased in recent years. Due to the particularity and diversity of its bleeding sites, the early treatment of hematoma needs to be more meticulous and accurate, and minimally invasive surgery is often one of the measures that are commonly adopted now. The lower hematoma debridement and the navigation template created by 3D printing technology were compared in the external drainage of a hypertensive cerebral hemorrhage. Then the effect and feasibility of the two operations were explicitly evaluated. Material and methods: We performed a retrospective analysis of all eligible patients with HICH who underwent laser-guided hematoma evacuation or hematoma puncture under 3D-navigated molds at the Affiliated Hospital of Binzhou Medical University from January 2019 to January 2021. A total of 43 patients were treated. Twenty-three patients were treated with laser navigation-guided hematoma evacuation (group A); 20 patients were treated with 3D navigation minimally invasive surgery (group B). A comparative study was conducted between the two groups to evaluate the preoperative and postoperative conditions. Results: The preoperative preparation time of the laser navigation group was significantly shorter than that of the 3D printing group. The operation time of the 3D printing group was better than that of the laser navigation group (0.73 ± 0.26 h vs. 1.03 ± 0.27 h P=0.00070). In the improvement in the short-term postoperatively, there was no statistically significant difference between the laser navigation group and the 3D printing group (Median hematoma evacuation rate P = 0.14); And in the three-month follow-up NIHESS score, there was no significant difference between the two (P = 0.82). Conclusion: Laser-guided hematoma removal is more suitable for emergency operations, with real-time navigation and shortened preoperative preparation time; hematoma puncture under a 3D navigation mold is more personalized and shortens the intraoperative time course. There was no significant difference in therapeutic effect between the two groups.